NILAI-NILAI AKHLAK DALAM FILM “CAHAYA CINTA PESANTREN” DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM - Triana Iradatul Jannah; Mohammad Farah Ubaidillah (Fakultas Agama Islam Universitas Islam Madura, 2022)
Morals in everyday life occupy a very important position. Therefore, there is a need for moral formation of a person through education and moral development that can be carried out both in the school environment, family, and community so that the occurrence of moral decline can start early. One proof of the current technological sophistication that can provide education and moral formation to someone is the creation of a work of art in the form of a movie that is not only for entertainment, but also presents a message to be conveyed to the audience. An educator or parents can provide education and moral formation to students or children through a movie, for example Cahaya Cinta Pesantren movie which is the work of Indonesian children which presents many moral messages in it. At school environment, an educator through PAI subjects can use their learning resources by showing a movie such as Cahaya Cinta Pesantren movie as one of the learning media that can provide teaching about morals to the students. The method in this research uses content analysis which is carried out objectively and systematically which results in conclusions in the form of messages presented in a form of communication media in the form of movies. This research produces data on moral values ​​in the Cahaya Cinta Pesantren movie and how is the relevance between moral values ​​in Cahaya Cinta Pesantren movie with Islamic religious education.